Portland's Good Life: Sustainability and Hope in an American City - Stephenson, R. Bruce (Lexington Books, 2021)
Iconic urbanist Lewis Mumford stressed the role of a well-constructed city in the development of the good life, championing pedestrian-scaled, sustainable cities. In Portland's Good Life, R. Bruce Stephenson examines how Portland, the one city in America that adopted Mumford’s vision, became a model city for living the good life. Stephenson traces Portland’s success to its grass roots governing system, its housing and climate protection initiatives, and most of all, its citizens devoted to the public good; all of which have resulted in the construction of a city that honors the humanity of its people.